Application of Waste Heat Recovery Systems for Evaluating the Effectiveness and Electrical Energy Consumption Seaweed Convective Dryer - Nicolas - Titahelu; Raja Bonan Dolok Sormin; Wulfilla Maximilian Rumaherang; Jandri Louhenapessy; Cendy Sophia Edwina Tupamahu; Nataliano Resky Inuhan (Diponegoro University, 2026)
The research has practical implications for the design and operation of seaweed convective dryers, particularly in the context of energy conservation. Implementing a Waste Heat Recovery System (WHRS) to utilize waste heat from convective dryers that have been wasted into the environment is a promising development. This research aims to obtain the effective air velocity at which the effectiveness of the seaweed convective dryer is at its maximum and obtain drying time and minimum electrical energy consumption for operating conditions with and without the application of WHRS. The experimental method was carried out by varying the air velocity value from 1 to 5 m/s at certain temperatures, heat input, and humidity. Capturing and recording measured data after reaching steady conditions. The experimental results show that effectiveness decreases as air velocity increases, where the maximum effectiveness at minimum air velocity is 46.83% and 46.61% for operating conditions with and without WHRS implementation, where the average deviation value is 1.38%. On the other hand, drying time and minimum electrical energy consumption are at a maximum air velocity of 20.97 hr and 21.25 hr, respectively, and 19 kWh and 19.45 kWh for operating conditions with and without WHRS application, where the deviation of the average value in electrical energy consumption is 1.98%. It was concluded that the maximum air velocity can be used for convective drying of seaweed by applying WHRS, presenting a new and exciting approach to seaweed drying with significant potential benefits for energy conservation.